A Review on the Optimization of Porous Glass-Ceramics Through a Mixed-Method Approach (Journal of Applied Science, Engineering and Technology, 2025)
This review investigates the optimization of the controlled crystallization process for porous glass-ceramic materials, with a focus on basalt-based compositions, to enhance their mechanical and thermal properties for functional applications such as thermal insulation and lightweight structural components. A critical gap identified in the current literature is the lack of comprehensive studies that integrate process parameters, pore structure, and material performance. Additionally, the potential of local materials such as basalt, particularly in the context of Indonesia’s abundant basalt reserves, remains underexplored. This review synthesizes findings from studies employing a mixed-method approach, combining quantitative experimental designs that evaluate the influence of key variables—temperature, heating time, and composition—on the crystallization process and pore formation in glass-ceramics. The findings aim to provide a more nuanced understanding of process-property relationships and contribute to the development of sustainable, energy-efficient basalt-based ceramic materials. The insights presented are expected to inform the formulation of practical and efficient production strategies, driving the application of porous glass-ceramics in industrial sectors as advanced materials.